The scope of war crimes against peace-keeping personnel : Do Articles 8 (2) (b) (iii) and (e) (iiD ICC- Statute and 4 (b) SCSL- Statute fulfil the requirements of the principle of specificify in international law? - Seifert, Katharina Elena (Department of Public Law, 2015)
Includes bibliographical references.